Pragmatizam EU pri instrumentalnoj utilizaciji institucionalizacije podataka / Pragmatism of the EU in Instrumental Utilization of Data Institutionalization - Dinarević, Mirza (Pregled: časopis za društvena pitanja / Periodical for social issues, 2025)
This paper is comprised of the following parts: Introduction, Stable institutionalization as the answer, The foundation of institutionalization, How close is institutionalization to the EU? The EU's institutionalization through soft law and Conclusions/considerations. Using primarily legal but also economic analytical methodology, it will be illustrated that despite the criticism of international institutions and institutionalization in general, it is important to understand their usefulness and purpose in the larger scheme of things when it comes to digital trade, i.e. data. Although, in legal circles, institutionalization is understood to be embryonic with connotations of it being ‘thin’ or ‘thick’, it is largely dependent on the executive understanding of norms and their capacity for development and interpretation. There is no self-evident form for the institutionalization of regional trade integrations. A taxonomy or selection of options or best practices does not exist. It will be highlighted that there is no hard and fast rule on regulatory coherence and institutionalization that has a direct impact on the ‘thickness’ of institutional design, which does not necessarily mean dynamic transnational or supranational governance. Ultimately, a thread is revealed that connects the work of the European Court of Justice, national courts and significant institutional enforcement in the form of the emergence of new forms of economic integration based on looser forms of intergovernmental relations but also a turn away from ‘thick’ forms of institutionalization, in effect moving away from EU models.